2019
DOI: 10.1007/s13205-019-1709-5
|View full text |Cite
|
Sign up to set email alerts
|

Matrix attachment regions as a tool to influence plant transgene expression

Abstract: The inclusion of special regulatory sequences known as matrix attachment regions (MARs) in transgene constructs has been suggested as a possible approach to stabilise the expression of foreign heterological genes. The present review provides a brief summary regarding the MARs that have been used in investigations studying their influence on plant transgene expression in different plants with different promoters and reporter genes, and the comparison of these investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…One likely reason could be that the variability in transgene expression is influenced not only by the copy number of transgene within the integration site but also by the chromatin status (heterochromatic or euchromatic). Additionally, transgene expression could be affected by nearby regulatory sequences, such as enhancers or silencers (Dolgova and Dolgov, 2019). Although the results of the sqRT-PCR analysis showed that every fluorescent gene was transcribed into RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One likely reason could be that the variability in transgene expression is influenced not only by the copy number of transgene within the integration site but also by the chromatin status (heterochromatic or euchromatic). Additionally, transgene expression could be affected by nearby regulatory sequences, such as enhancers or silencers (Dolgova and Dolgov, 2019). Although the results of the sqRT-PCR analysis showed that every fluorescent gene was transcribed into RNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear matrix attachment regions (MARs) are A/T-rich DNA sequences of approximately 400 bp found at the borders of nontranscribed genes that mediate the structural organization of chromatin within the nucleus (Dolgova and Dolgov, 2019). MAR sequences have been used to flank MCs to reduce transgene silencing, improve expression stability (Zhang et al, 2004;, and enhance transformation efficiency (Petersen et al, 2002).…”
Section: Binary and Alternative Vectorsmentioning
confidence: 99%
“…MARs are often correlated with chromatin features like, AT richness, the origin of replication, etc., and are also hotspots for transposable element insertions (6). Many studies have been carried out determining their role in the maintenance of chromatin architecture, stabilization and regulation of gene expression (7)(8)(9) and their in uence on gene silencing mechanisms (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%